Beneficial effects of moderate exercise on mice aging: Survival, behavior, oxidative stress, and mitochondrial electron transfer - Navarro, Ana (2004)
Moderate exercise in a treadmill (10, 15, and 20 cm/s, for 5 min each, weekly) from 28 to 78 wk of age extended male and female mice life span by 19 and 9% accompanied by 36 and 13% and 13 and 9% increased performance in behavioral assays (tightrope and T-maze tests) at 52 wk of age. Moderate exercise significantly decreased the aging-associated development of oxidative stress by preventing 1) the increase in protein carbonyls and thiobarbituric acid-reactive substances contents of submitochondrial membranes; 2) the decrease in antioxidant enzyme activities (Mn- and Cu,Zn- superoxide dismutase and catalase); and 3) the decrease in mitochondrial NADH-cytochrome-c reductase and cytochrome oxidase activities observed at 52 wk of mice age in brain, heart, liver, and kidney. These effects were no longer significant at 78 wk of age in mice. Moderate exercise, started at young age in mice, increased life span, decreased oxidative stress, and prevented the decline of cytochrome oxidase activity and behavioral performance at middle age but not at old age.